If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4xy + -2y(x + 1) = 0 Reorder the terms: 4xy + -2y(1 + x) = 0 4xy + (1 * -2y + x * -2y) = 0 Reorder the terms: 4xy + (-2xy + -2y) = 0 4xy + (-2xy + -2y) = 0 Combine like terms: 4xy + -2xy = 2xy 2xy + -2y = 0 Solving 2xy + -2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 2xy + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 2xy + 0 = 0 + 2y 2xy = 0 + 2y Remove the zero: 2xy = 2y Divide each side by '2y'. x = 1 Simplifying x = 1
| 2(2w-6)=6(w-16)+14 | | -4x-9y=1 | | 16-7m=5m-4m | | 180-76=b | | 3*cos(2x)-5*cos(x)=1 | | x+69=166 | | 4c+d=20 | | 5x+2x=90 | | 3x-2(5.091)=4 | | 13inches= | | 36=3(x+5) | | 12x+-11x=-18 | | 6x^4-6=0 | | 13*8+73= | | 6c=40 | | -25=y-13 | | 10-k+3k=4k+2 | | 15x+22=120 | | 5x-1+x=17 | | x+9+4x=-11 | | 10+2y=28 | | 5x-1+x= | | 10x+2y=28 | | 11s-4s-6s=17 | | 1.06s-0.01(248.4-s)=22.67s | | 32=8-4x-5x | | 21-2y=-2 | | 4x+12=2(4x+11) | | 70=5(x-2) | | 7x+(6x-1)+90=180 | | X+-17=1 | | 11(z+4)-4(z-3)=3(z-1)+3(z-3) |